Moderating effect of logistics and supply chain issues on the relationship between entrepreneurial orientation and market orientation - Nik Abdullah, Nik Ab. Halim; Yaakub, Sabariah; Subhan, Muhammad (RMP Publications, 2018)
Business expansion either locally or internationally is a vision of most firms, even for small and medium sized enterprises (SMEs). In order to achieve this market expansion, previous studies have identified the importance of market orientation towards superior firms’ performance. At the same time, firm-level market orientations are also important. However, the existence of logistics and supply chain issues such as transportation, packaging, documentation and warehousing are expected to thwart firms’ effort in establishing their market orientation. This study focuses on identifying the effect of logistics and supply chain related issues on the relationship between entrepreneurial orientation and market orientation among SMEs in Malaysia. The result indicates that logistics and supply chain issues moderate the relationship between entrepreneurial orientation and market orientation. However, the moderation effect is weak, based on the Cohen f2 effect size calculation. This study shows that logistics and supply chain issues do have some weak effect on the relationship between both variables. Thus, SME managers need to resolve any logistics and supply chain related issues experienced by the company in order to improve their market orientation